Clinical Practice Guidelines of Integrated Chinese and Western Medicine Rehabilitation for Spinal Cord Injury - WANG Chuhuai; YANG Jiajia; CHENG Xue; SHEN Ying; SU Min; ZOU Jun; GAO Xiaoyu; CHEN Long; HUANG Sisi; ZHOU Ting; LI Xin; WANG Hongxing (康复学报)
Spinal cord injury (SCI) is a destructive neuropathological condition characterized by the temporary or permanent impairment of spinal cord function, resulting in motor, sensory, and autonomic dysfunctions. Based on the principles of evidence-based medicine, the development of clinical practice guidelines of integrated Chinese and western medicine rehabilitation for SCI can provide clinicians with a comprehensive and standardized framework for SCI treatment and rehabilitation. This scientific, standardized and unified practice guideline covers the technical scope, normative references documents, terms and definitions, SCI classifications and clinical diagnosis, rehabilitation assessment, rehabilitation diagnosis and treatment program and treatment of common complications, etc. Rehabilitation assessment of SCI mainly includes sensory examination, motor examination, motor or sensory function rating, quality of life assessment, functional assessment and psychological function assessment (stress assessment, cognitive function assessment, and emotional state assessment). Rehabilitation diagnosis and treatment program of SCI mainly includes early treatment principles, drug therapy, physical therapy (muscle strength training, balance and gait training, aerobic exercise, electrical stimulation and other therapies), occupational therapy (joint range of motion training, activities of daily living training, resting motor skill training, upper limb function training and wheelchair skills training), assistive devices, traditional Chinese medicine therapy, including single drug therapy (ligustrazine, salvia miltiorrhiza injection, roasted nux vomica, etc.) and compound therapy (salvia miltiorrhiza ligustrazine injection, Buyang Huanwu decoction, Huoxue Tongdu decoction, erxian decoction, Yiqi Huoxue decoction and self-formulated decoction, etc.), acupuncture therapy and other therapies (new drug therapy, cell therapy, neuromodulation technology and brain-spine interface technology). Common complications of SCI include autonomic hyperreflexia, deep vein thrombosis, heterotopic ossification, orthostatic hypotension, pressure ulcers and urinary tract infection. This guideline can provide guidance for all kinds of rehabilitation institutions at all levels as well as the department of orthopedics and traumatology of traditional Chinese medicine, department of orthopedics of integrated traditional Chinese and western medicine, acupuncture and moxibustion department, Tuina department and rehabilitation medicine department in the hospitals of traditional Chinese medicine or general hospitals in China to perform SCI clinical diagnosis, rehabilitation assessment, rehabilitation treatment and treatment of common complications, with good clinical applicability, safety and effectiveness.